REPRESENTASI PEREMPUAN DALAM STAND UP COMEDY (Analisis Semiotika Pierce dalam Tayangan Annie Yang) - Pranawukir, Iswahyu; Misnan, Misnan; Sukma, Agus Hitopa; Desilawati, Nur; Barizki, Rezzi Nanda; Astanto, Agung Pramudi (SEMIOTIKA: Jurnal Komunikasi, 2024)
"Stand Up Comedy" in parts or parts on Annie Yang's show is a short film produced which is then uploaded to the Youtube channel. Annie Mariani, known as the comedian Annie Yang of Chinese descent, established her career in Taiwan and came from Bali Comedy Club. A graduate of Stand Up Comedy Indonesia held by Kompas.TV. Her jokes or anecdotes tend to use English and Annie is nicknamed naughty girl or naughty woman.The use of feminism studies combined by the author with the qualitative method of Charles Sanderpierce's semiotic analysis means that a sign is something that for one woman represents something else in some way or capacity. And one form of sign is the word, while the object is something that is referred to by the sign, while the interpretant is a sign that exists in a person's mind about the object that a sign refers to. By observing and analyzing in the initial observation that the jokes thrown by Annie Yanng are more pouting, double standard meaning depending on the audience as communicators interpret the core message in the context and content of the message. It can be positive and negative depending on which side of the audience understands it so that it provokes laughter.